Becoming a “you tuber” as pedagogical proposal for improving the oral fluency in english language classroom. (2020)
SUMMARY: The purpose of this project is to improve the oral fluency in students from fifth grade at “Santa Luisa School” in Bogota D.C. through the YouTube platform and the union with ICT (information and communication technology) as strategy. Also motivate learners to use the target language in a real situation using web games, podcast, video games and information about intercultural background to improve their knowledge, structures, vocabulary and certainly the speaking ability. Through this project the educator is going to be the model who uses different strategies, vocabulary and the proposal topics that students will talk about and show them through audiovisual material. In this way, students will improve their fluency at the moment they express their ideas and thoughts. Besides, this project will help and analyze the impact of the fluency that the learners can get through the different strategies applied, where the teacher is the leader and assumes the role of being a guide for the learners to improve speaking skill. Firstly, the students will be examined through the diagnostic test to know their previous knowledge. Secondly, the mistakes will be analyzed but across the project they will be improved by the implementation of different learning strategies and activities to improve the student’s oral skill and will able to speaking with fluency. On the other hand, students during the work get funnier and confident because they will enjoy the proposal activities using CALL (computer-assisted language learning) with web games, YouTube videos, simulation activities, role-plays, and some strategies such rehearsal, repetition, consciousness-raising to improve the oral fluency.